NFE in Rural Areas – An Experiential Account - Kaur, Harpreet (THE PRIMARY TEACHER, 2006)
NFE, Non-formal Education, in a semi urban village area has aspects of uneven development. It has communal, caste, and political colour. As a teacher the experience of applying innovative educational approaches to make learning more meaningful was enriching, real, and satisfying. The role of NGOs and the community is critical in starting an sustaining educational programme. However, how the programme is to be continued, and how education is to be conceptualised, remains masked. This is where the approaches deviated from the community’s participation, needs, and demands.